Functional Contributions of Antigen Presenting Cells in Chronic Graft-Versus-Host Disease - Hong, Chao; Jin, Rong; Dai, Xiaoqiu; Gao, Xiaoming (Frontiers in Immunology, 2021)
Chronic graft-versus-host disease (cGVHD) is one of the most common reasons of late non-relapse morbidity and mortality of patients with allogeneic hematopoietic stem cell transplantation (allo-HSCT). While acute GVHD is considered driven by a pathogenic T cell dominant mechanism, the pathogenesis of cGVHD is much complicated and involves participation of a variety of immune cells other than pathogenic T cells. Existing studies have revealed that antigen presenting cells (APCs) play crucial roles in the pathophysiology of cGVHD. APCs could not only present auto- and alloantigens to prime and activate pathogenic T cells, but also directly mediate the pathogenesis of cGVHD via multiple mechanisms including infiltration into tissues/organs, production of inflammatory cytokines as well as auto- and alloantibodies. The studies of this field have led to several therapies targeting different APCs with promising results. This review will focus on the important roles of APCs and their contributions in the pathophysiology of cGVHD after allo-HSCT.